Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/apps.12299
|View full text |Cite
|
Sign up to set email alerts
|

Rain, Rain Go Away! A Diary Study on Morning Weather and Affective Well‐Being at Work

Abstract: Weather determines a number of affective experiences in everyday life. Although affective events theory positions environmental features such as the weather as important in determining affective well‐being also at work, research in this regard has mainly focused on predictors within the person or work context. Addressing this gap, we studied how daily morning weather relates to day‐specific affective well‐being at work. Specifically, we examined vigor and job satisfaction as positive well‐being states, and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…It is likely that there are periods of higher levels of burn-out syndrome risk and recovery need during a normal school year, possibly influenced by the weather and seasonal conditions. Previous research showed the weather to have an impact on depression ( 57 ), job satisfaction and wellbeing ( 58 ), while seasonal conditions may influence anxiety ( 59 ) and depression ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that there are periods of higher levels of burn-out syndrome risk and recovery need during a normal school year, possibly influenced by the weather and seasonal conditions. Previous research showed the weather to have an impact on depression ( 57 ), job satisfaction and wellbeing ( 58 ), while seasonal conditions may influence anxiety ( 59 ) and depression ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we observed that two disengagement items, namely 3D (Today, I thought less at work and did my job almost mechanically) and 6D (Sometimes I felt sickened by my today work tasks), had particularly low factor loadings. A relevant comparative empirical material is lacking since no factor analysis was reported in the available studies on daily burnout [62][63][64][65][66]. Nonetheless, the results from classical confirmatory factor analysis [37,39,49] show that while the 3D item loadings indicate general satisfactory values (e.g., .64-.82), the range for the 6D item is less conclusive (e.g., .49-.76).…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of these within-person studies is that they mostly used the MBI to measure burnout. We found only five daily diary studies, in which symptoms of burnout were assessed with the OLBI [62][63][64][65][66], though these were mainly limited to measurement of exhaustion. Only two assessed both components of burnout, but the OLBI was shortened to 12 [63] and 6 items [65], without further specifying them.…”
Section: Job Burnout As Trait Versus Statementioning
confidence: 99%
“…To capture participants' state vigour both at the end of the workday and at bedtime, we used four items of the physical strength subscale of the German version of the Shirom-Melamed Vigour Measure (Shirom, 2004) in a version adapted for daily assessment (Venz & Pundt, 2021). A sample item is 'I feel full of energy'.…”
Section: Vigourmentioning
confidence: 99%